Comparison of Low-Molecular-Weight Heparins Prepared From Bovine Heparins With Enoxaparin. (September 2017) - Liu, Xinyue; St.Ange, Kalib; Fareed, Jawed; Hoppensteadt, Debra; Jeske, Walter; Kouta, Ahmed; Chi, Lianli; Jin, Caijuan; Jin, Yongsheng; Yao, Yiming; Linhardt, Robert J.
Heparin and its low-molecular-weight heparin (LMWH) derivatives are widely used clinical anticoagulants. These drugs are critical for the practice of medicine in applications including kidney dialysis, cardiopulmonary bypass, and in the management of venous thromboembolism. Currently, these drugs are derived from livestock, primarily porcine intestine. The worldwide dependence on a single animal species has made the supply chain for this critical drug quite fragile, leading to the search for other sources of these drugs, including bovine tissues such as bovine intestine or lung. A number of laboratories are currently examining the similarities and differences between heparins prepared from porcine and bovine tissues. The current study is designed to compare LMWH prepared from bovine heparins through chemical β-elimination, a process currently used to prepare the LMWH, enoxaparin, from porcine heparin. Using top-down, bottom-up, compositional analysis and bioassays, LMWHs, derived from bovine lung and intestine, are shown to closely resemble enoxaparin.